Forty acres and maybe a mule - Robinet, Harriette (New York : Atheneum Books for Young Readers, 1998)
Born with a withered leg and hand, Pascal, who is about twelve years old, joins other former slaves in a search for a farm and the freedom which it promises
"A Jean Karl book."
Includes bibliographical references (p.132).
610
Accelerated Reader AR
Keywords: African Americans -- Juvenile fiction; Reconstruction -- Juvenile fiction; African Americans -- Fiction; Reconstruction -- Fiction; Slavery -- Fiction; Disabilities -- Fiction; United States -- History -- 1865-1898 -- Juvenile fiction; United States -- History -- 1865-1898 -- Fiction